Systemic mitigation of salt stress by hydrogen peroxide and sodium nitroprusside in strawberry plants via transcriptional regulation of enzymatic and non-enzymatic antioxidants - Christou, Anastasis; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2014)
Nitric oxide (NO) and hydrogen peroxide (H2O2) have a pivotal role in plant development and stress responses, thus rendering them as key molecules for priming approaches. In this study, a hydroponic experiment was employed in order to investigate the effects of NO donor, sodium nitroprusside (SNP; 100 μM), or H2O2 (10 mM) root pretreatment in major components of redox homeostasis and signaling of strawberry plants (Fragaria × ananassa cv. ‘Camarosa’) exposed immediately, or 7 d after root pretreatment, to salt stress (100 mM NaCl, 8 d). Plants stressed immediately after root pretreatment with either reactive species demonstrated increased chlorophyll fluorescence, photosynthetic pigment content, leaf relative water content as well as lower lipid peroxidation and electrolyte leakage levels in comparison with plants directly subjected to salt stress, suggesting a systemic mitigating effect of NO/H2O2 pretreatment to cellular damage derived from abiotic stress factors. In addition, primed plants managed to mitigate the oxidative and nitrosative secondary stress and redox homeostasis disturbances, since H2O2 and NO were quantified in lower levels, whereas ascorbate and glutathione redox states in leaves were sustained at higher rates, compared with NaCl treatment. Gene expression analysis revealed that priming effects of both H2O2 and NO root pretreatment correlated with increased transcript levels of enzymatic antioxidants (cAPX, CAT, GR, MnSOD, MDHAR and DHAR), as well as ascorbate (GaIUR, GLDH, GDH, MIOX) and glutathione biosynthesis (GCS, GS) in leaves, in contrast with the general transcriptional suppression observed in plants stressed without pretreatment, or 7 d after root pretreatment. Overall, pretreated plants displayed redox regulated defense responses leading to systemic tolerance to subsequent salt stress exposure.
Keywords: Ascorbate; Fragaria × ananassa; Glutathione; Nitrosative stress; Oxidative stress; Priming